Pengaruh Faktor Meteorologi terhadap Penerbangan Hama Padi Tertangkap pada Lampu Perangkap Merkuri dan CFL - EFFENDI, BAEHAKI SUHERLAN; RUSTIATI, TITA; ISWANTO, EKO HARI; SUMARYONO, NONO (Agrotrop : Journal on Agriculture Science, 2015)
The influence of meteorological factors on the rice pests flight that catched in the lighttraps of mercury lamp and CFL. Research was carried out in the 2013 at the experimentalgarden of Sukamandi, Indonesian Center for Rice Research (ICRR). Pests were catched in thelight traps of mercury lamp ML 160 watt and CFL 20 watt, while the meteorological data wascollected from a meteorological cage closed 200 m of the light trap. The objectives of thisresearch was to analyze the influence of meteorological factors on the pests flights as basicllyfor early warning system, forecasting and pests dispersal. The results showed that themeteorological factors such as evaporation, wind velocity, light intensity, air temperature,relative humidity, rainfall, and soil temperature at 0 cm were correlated one to anothers. Themeteorological factors had insignificant effect to pests flight of rice yellow stem borer, ricepink stem borer, rice black bug, and brown planthopper that catched in the lihgt trap ofmercury lamp and CFL. Evaporation and soil temperature at 0 cm had significant positiveinfluence while relative humidity had significant negative influence on the flight of leaf folderthat catched in the lihgt trap of mercury lamp. In the lihgt trap of CFL bulbs, the flight of leaffolder had significant positive influenced by air temperature and soil temperature at 0 cm,while had significant negative influenced by relative humidity and rainfall.
Keywords: light trap; meteorological factors; rice pests